Isolation, characterisation and quantification of the main oligomeric macrocyclic ellagitannins in Epilobium angustifolium by ultra-high performance chromatography with diode array detection and electrospray tandem mass spectrometry - Nicolas Baert; Maarit Karonen; Juha-Pekka Salminen (Elsevier, 2022)
Abstract Tannins have beneficial effects in animal nutrition as they are able to decrease methane emission in ruminants and exert anthelminthic activity against intestinal nematodes. However, tannins can have very diverse structures and therefore, different activities. In order to enhance the research in tannin-rich forages we need tools which are able to quantify tannins individually. In this study we isolated and characterised the main tellimagrandin I (TI)-based oligomeric ellagitannins (ETs) from Epilobium angustifolium (willowherb) and developed a UHPLC-DAD–ESI-MS/MS method to quantify them in plant extracts. The mass spectrometer was operated in Multiple Reaction Monitoring mode to enable the selective detection of dimeric to heptameric ETs from the plant extract. The method proved to be sensitive, with limits of detection ranging from 0.1 to 1.3 μg mL−1. The stability test showed a good repeatability with an inter-run deviation of the results from 0.1 to 5%, except for the pentamer and hexamer where it reached 8%. The method was then successfully applied to evaluate the distribution of those ETs in the plant. This work also provides the first time evidence of the presence of tetrameric to heptameric TI in willowherb.